Aggregation of asphaltene model compounds using a porphyrin tethered to a carboxylic acid1. Issue 25 (7th July 2015) - Schulze, Matthias; Lechner, Marc P.; Stryker, Jeffrey M.; Tykwinski, Rik R.
<x xml:space="preserve">Abstract</x> Two model compounds are used in NMR spectroscopic studies to probe aggregation toward unraveling the mysteries of intermolecular interactions in asphaltenes, which are the heaviest portions of petroleum.